A case of paradoxical reaction after treatment of generalized tuberculous lymphadenopathy in a peritoneal dialysis patient. (March 2022) - Khan, Farah Gul; Fan, Stanley
Paradoxical reaction (also known as Jarisch–Herxheimer reaction) is a self-limited response to endotoxin released from dead bacteria after starting treatment and is characterized by constitutional symptoms such as fever, headache, dizziness and exacerbation of cutaneous lesions. We report a rare case of a 55-year-old gentleman, on peritoneal dialysis, who developed fever, dizziness and cloudy dialysate after starting anti-tuberculous treatment for disseminated tuberculous lymphadenitis. He was started on antibiotics for suspected peritoneal dialysis peritonitis and anti-tuberculosis treatment was continued. However, all his cultures turned out negative including peritoneal 16S ribosomal RNA. The diagnosis of paradoxical worsening following anti-tuberculosis treatment was made. His peritoneal dialysis was continued and he made full recovery after 8 months of therapy. This case highlights the fact that in a peritoneal dialysis patient, paradoxical reaction can present as cloudy dialysate with raised infective markers.